Kemampuan Guru Bahasa Indonesia dalam Mendesain Rencana Pembelajaran Teks Laporan Observasi di Kecamatan Sekongkang - Nursainah; Mahsun; Burhanuddin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to 1). How is the teacher's ability to develop indicators of Learning Text Observation reports from basic competencies?; 2). How is the teacher's ability to determine the learning material of the observation report text that is by the indicators; and 3). What is the teacher's ability to determine the appropriate learning method with the learning material? This type of research uses a qualitative descriptive method. This study describes the preparation of learning implementation plans by Indonesian language teachers. The sample in this study amounted to 5 Indonesian language teachers. From the results of research and analysis of research data, it is found that the ability of teachers to design learning designs that are by the material in the classroom is very important to achieve the educational goals to be achieved. Because educators in each educational unit are obliged to compile a complete and systematic lesson plan so that learning can take place interactively, inspiring, fun, challenging, efficient, motivating students to participate actively, and providing sufficient space for the initiative, creativity, and independence by with the talents, interests, and physical and psychological development of students. Therefore, it is very important to master the teacher's mastery in implementing lesson plans in the classroom. Because with the mastery of lesson plans, class learning will be effective. However, several things still escape the attention of the teacher, namely, the teacher does not consistently carry out apperception activities. Sometimes apperception delivery activities are still forgotten from the teacher's attention. Teachers need to pay attention and utilize the time allocation to complete learning to the maximum so that each learning activity can be carried out properly